Contaminación con metales pesados en sedimentos y truchas en los ríos Opamayo y Sicra, Huancavelica-Perú - Quispealaya Armas, Luis (2021)
The objective was to determine the concentration of heavy metals in sediments and troutin the Opamayo and Sicrarivers; the problem is, harmful metallic existence in hydric life, the methodology was applied, developed with specialists in mining, chemistry, environment; In the field, samples were collected in aquatic channels, in the laboratory with sieving techniques, analytical balance; and THERMOCIENTIFIC ISO 3000 SERIES Atomic Absorption Spectrophotometer; The following sediments resulted: Lead (Pb = 0.07 mg / L), arsenic (As =0,04 mg/L), cadmium (Cd = 0,013 mg/L), chromium (Cr = 0,05 mg/L); being below the maximum permitted level Supreme Decree D.S.N° 0015-2015-MINAM. The heavy metal concentrations in trout in the Opamayo River exceed those of the Sicra River: In arsenic 0.804 mg/kg, cadmium in 0,086 mg / kg, chromium in 0,227 mg / kg and lead in 1,659 mg / kg concentration; therefore: According to CODEX STAN 193-1995 "Standard for contaminants and toxins in food and feed"; on average they are below the maximum permissible limits. In conclusion, in both rivers are heavy metals, but; in Opamayo aquifers, contaminated by mining, there is a higher concentration.